A NEED FOR ADULT AND GERONTOLOGICAL EDUCATION IN THE PREPARATION OF PERUVIAN TEACHERS - Rodríguez del Solar, Natalia (2014)
In order to educate outstanding future educators for the country, we have incorporated innovations to our curricular plans stemming from the sciences of Andragology (educating adults) and Gerontology (educating mature adults). At present, Peruvian universities focus on preparing specialized teachers for elementary (children) and high school (adolescents) levels. However, there is a lack of preparing teachers to educate adults and mature adults.